Whole‐body biomechanical differences between limbs exist 9 months after ACL reconstruction across jump/landing tasks. (6th August 2018) - King, Enda; Richter, Chris; Franklyn‐Miller, Andy; Daniels, Katherine; Wadey, Ross; Moran, Ray; Strike, Siobhan
Abstract : Introduction: Previous studies examining jump tasks after anterior cruciate ligament reconstruction (ACLR) have focused on performance measures without examining joint kinematic and kinetic variables. The aim of this study was to identify differences in biomechanical and performance measures between limbs across tests 9 months after surgery. Methods: Four jump tests (double‐leg drop jump (DLDJ), single‐leg drop jump (SLDJ), single‐leg hop for distance (SLHD) and hurdle hop (HH)) were carried out on 156 male subjects in a 3D motion capture laboratory 9 months after surgery. Statistical parametric mapping was used to identify differences in jump performance and biomechanical variables between limbs. Results: Biomechanical measures were lower on the ACLR side across all four tests for internal knee valgus moment (effect size (ES) 0.77‐0.92), knee internal rotation angle (ES 0.59‐0.8), and ankle external rotation moment (ES 0.59‐0.73), with the center of mass less posterior to the knee during the single‐leg tests (ES 0.61‐0.82). The timing of the largest difference between limbs was not at the same % stance between variables within a test or for any variable across tests. Large ES differences were observed in performance in the SLDJ (ES 0.73‐0.81; LSI 78%) and small differences in the SLHD (ES 0.36; LSI 94%) between the limbs. Conclusion: Findings highlighted biomechanical differences between limbs which are consistent across jump tasks suggesting insufficient rehabilitation at 9 months post surgery. Results indicate that the SLDJ may identify greater performance deficits between limbs than SLHD, which may over‐estimate rehabilitation status.